2005
DOI: 10.1093/ndt/gfh875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antioxidant supplementation on blood cyclosporin A and glomerular filtration rate in renal transplant recipients

Abstract: In CsA-treated RTRs, antioxidant supplementation decreased blood CsA, which may affect adequacy of immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 19 publications
2
11
0
3
Order By: Relevance
“…Our results approve the results of Benito B (12) report in which studied effect of vitamin C in liver protein pattern of CsA-treated rats. Although this study shows the beneficial effect of vitamin C in decreasing CsA-induced liver toxicity it has been suggested that antioxidant supplementation is beneficial only when elevated oxidative stress is present (13) because some studies show that the co-administration of antioxidants like vitamin C may decrease CsA dose in the body and interfere with the aim of using CsA regimen in patients (14). In conclusion, we have shown that vitamin C administration provides pro-tection against CsA-induced injury in rat liver function and it may have hepatoprotective role in patients experiencing CSA treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Our results approve the results of Benito B (12) report in which studied effect of vitamin C in liver protein pattern of CsA-treated rats. Although this study shows the beneficial effect of vitamin C in decreasing CsA-induced liver toxicity it has been suggested that antioxidant supplementation is beneficial only when elevated oxidative stress is present (13) because some studies show that the co-administration of antioxidants like vitamin C may decrease CsA dose in the body and interfere with the aim of using CsA regimen in patients (14). In conclusion, we have shown that vitamin C administration provides pro-tection against CsA-induced injury in rat liver function and it may have hepatoprotective role in patients experiencing CSA treatment.…”
Section: Discussionmentioning
confidence: 81%
“…L'effet uricosurique de la vitamine C est probablement en rapport avec des interactions avec un transporteur d'urates, tel que URAT1. Une étude randomisée contrôlée versus placebo en simple insu chez des receveurs de reins avait montré que la supplémentation antioxydante par de la vitamine C, la vitamine E et la ␤-carotène pouvait améliorer la filtration glomérulaire ainsi que les chiffres de la créatinine sérique [24]. Huang et al ont rapporté que la vitamine C augmentait le débit de filtration glomérulaire chez les personnes traitées par la vitamine C (500 mg/jour) comparativement au placebo [11].…”
Section: Variablesunclassified
“…Furthermore, aT injection also increased expression of multidrug resistant protein 1 (MDR-1), a transporter protein which also aids the elimination of xenobiotics from the liver via biliary excretion (Mustacich et al, 1998). There have been recent studies showing that vitamin E supplementation (either alone or co-administered with other antioxidants) could decrease the concentration of cyclosporine A (an immunosuppressant known to be metabolised by CYP3A4) in healthy volunteers and renal transplant recipients (Barany et al, 2001;Blackhall et al, 2005;de Vries et al, 2006). Decreasing cyclosporine A concentration may lead to increased organ rejection in transplant patients (de Vries et al, 2006).…”
Section: Vitamin E Metabolism and Drug Interactionsmentioning
confidence: 99%